Gambaran Faktor Penyebab Menarche Dini pada Siswi SMPN 4 Kota Pariaman: Overview of Factors Causing Early Menarche in Students of SMPN 4 Pariaman City - Lili Fajria; Nengsih M. Desi (Fakultas Keperawatan Universitas Andalas, 2014)
Menarche is the first time menstruation comes as a result of ovulation which became one ofthe characteristics of puberty. Epidemiological studies point to the fact that the age of menarche ofwomen in various part of the world in recent times faster. This is a descriptive study to look at thepicture of the causes of early menarche in adolescents in SMP 4 Pariaman, the entire population ofstudents who experience early, menarche, amounting 51 people. The result showed picture of thecauses of early menarche in SMP 4 Pariaman is due to hereditary factors as much as 39,2 %, whichis exposed to environmental factors as much as 68,6 %, which is a good social-economic factors asmuch as 90.2 %, a factors that is not harmonies family as much as 86,3 %, factor in urban areaswhere as much as 86,3 % and physical activity factors that are not doing as much as 90,2%. Theresults above indicate that environmental factors, socioeconomic factors, factors residence, factorsfamily circumstances and factors of physical activity may be the cause of early menarche inadolescents, so it is advisable to family, school and relevant agencies in order to provide knowledgeto children through counseling about the presences of factors – these factors causes early menarchein adolescent and adolescent development stage is expected according to age.